War across the life course: examining the impact of exposure to conflict on a comprehensive inventory of health measures in an aging Vietnamese population. (4th January 2021) - Zimmer, Zachary; Fraser, Kathryn; Korinek, Kim; Akbulut-Yuksel, Mevlude; Young, Yvette Marie; Toan, Tran Khanh
Abstract: Background: The majority of evidence indicates that exposure to war and other traumatic events continue to have negative impacts on health across the life course. However, existing research on health effects of war exposure primarily concentrates on short-term impacts among veterans in high-income countries sent elsewhere to battle. Yet, most wars situate in lower- and middle-income countries, where many are now or will soon be entering old age. Consequently, the current burden of exposure to war has ignored an important global population. Methods: The Vietnam Health and Aging Study (VHAS) is a longitudinal study designed to examine historical exposure to highly stressful events during the American War. Two modes of data collection, involving a sample of 2447 individuals aged 60+ years in northern Vietnam, took place between May and August 2018. Using this first wave of data, we generate indexed measures of war exposure and analyze their associations with a set of 12 health outcomes, accounting for confounding variables. Results: Results indicate that greater exposure to three types of war exposure (death and injury, stressful living conditions, and fearing death and/or injury) in earlier life is associated with worse health in later-life across a large number of health outcomes, such as number of diagnosed health conditions, mental distress, somatic symptoms, physical functioning, post-traumatic stress symptoms and chronic pain. Conclusions: Findings support a life course theory of health and point to long-term effects of war on health that require detailed attention.